Design of Fe-based nanocrystalline alloys with superior magnetization and manufacturability. (January 2021) - Li, Hu; Wang, Anding; Liu, Tao; Chen, Pingbo; He, Aina; Li, Qiang; Luan, Junhua; Liu, Chain-Tsuan
Graphical abstract: Abstract: Fe-based alloys with a nanocrystalline-amorphous nanostructure exhibit superior soft-magnetic performances; however they generally suffer from the low magnetization because of their heavy doping for an acceptable manufacturability. In this study, we proposed a revolutionary nanostructure-construction concept based on preforming dense nuclei in the melt-quenching process with a critical cooling-rate and refining the nano-structure via transient metalloid-rich interfaces. A novel alloy composition of Fe85.5 B10 Si2 P2 C0.5 was developed via our multi-metalloid stabilization and critical formability strategies by using a total of only 4.6 wt. % light metalloids. This unique alloy design effort leads to unprecedented magnetic properties with the super-high B s of 1.87 T and µ e of 1.0–2.5 × 10 4, which outperform all commercial counterparts and have a high potential to substitute for commercial bulk Si-steels currently used for soft-magnetic applications. This hetero-structuring and lean-alloying strategy provides a paradigm for the next-generation of magnetic materials.